2d General Assembly, Illinois Territory, An Act Prohibiting Trade with the Indians (1813) - (:unkn) unknown (My University, 1813)
An act prohibiting the trading with Indians, Sec. 2: Prohibited trading or bartering a gun or other article commonly use for hunting with tribes. Also prohibited any instrument of husbandry or cooking utensil, or clothing or horse. Violators forfeit the item and pay any sum not less than ten nor exceeding fifty dollars.
Keywords: TRANSFER - DANGEROUS PERSONS